Pengaruh Penambahan Arang Tempurung Kelapa dan Bokashi Pupuk Kandang Terhadap Pertumbuhan Semai Akasia (Acacia Mangium Willd.) di Media Bekas Tambang Kapur - Basuki Wasis; Eranissa Islamika (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Continuous mining activities of limestone operation may cause negative impact such as environmental damage and reduction of soil quality (physically, chemistry, or biological). Revegetation is the process to increasing productivity of postmining limestose land. Acacia mangium is one of fast growing species that can grow in marginal land, symbitotic with rhizobium bacteria, and high economic value. The purpose of this research are to test the response of coconut shell charcoal and cow feces (bokashi) addition to the growth of akasia (Acacia mangium) seedling on postmining limestone soil and to find out the optimum dose of coconut shell charcoal and cow feces (bokashi) addition. This research used a complete randomized design factorial with two factors, each factor have four degree. First factor is addition of coconut shell charcoal and second factors is addition of cow feces (bokashi). The result of this research showed that coconut shell charcoal and cow feces (bokashi) addition on postmining limestone soil gives positive influence towards the amount of root nodule. But not affect other parameters such as height, diameter, total wet weight, total dry weight, and root tops ratio. The interaction between addition 10 g of coconut shell charcoal and 20 g of cow feces (bokashi) is the best composition for a significant effect in improving the amount of root nodule of A. mangium seedling by 78.58%. Very high levels of Ca in the soil medium will be toxic to the acacia plant.Keywords: Acacia mangium, bokashi cow feces, coconut shell charcoal, limestone mining